Liquid smoke application in latex as an environment-friendly natural coagulant. Issue 1 (November 2021) - Evahelda,; Astuti, R F; Aini, S N; Nurhadini,
Abstract: Liquid smoke has many benefits, especially in the food, fishery, timber, and plantation industries. It is used as a preservative or durability increased and aroma and taste addition in the food and fishery industry. In the wood industry, liquid smoke can resist termite attacks, while in the plantation industry, it functions as a latex coagulant containing antifungal, antibacterial, and antioxidants that can improve rubber product's quality. Most of the rubber farmers in Bangka Belitung still use alum as a coagulant to coagulate their latex. However, alum coagulant can reduce the quality of the processed rubber material (bokar). The reason farmers use alum is that raw materials are cheap, therefore getting coagulant raw materials at low prices and not pollute the environment with a less moderate aroma/odor caused by non-recommended coagulant materials (alum) are needed. This study aims to apply liquid smoke as a natural coagulant in latex freezing. The research method used a Completely Randomized Design, with liquid smoke concentration replicated three times. Parameters observed were clotting time speed and organoleptic test for odor during 14 days of storage. The results showed that the best concentration of liquid smoke was 15% no odor and a clotting time of 8.23 minutes.